Mischling, second degree : my childhood in Nazi Germany - Koehn, Ilse, 1929- (Hamish Hamilton, 1978)
The memoirs of a German girl who became a leader among the Hitler Youth while her Social Democratic family kept from her the secret of her partial Jewish heritage.